Energy and exergy performance of a solar-driven NH₃–NaSCN absorption refrigeration cycle: Case study in the Colombian Caribbean - Vanessa Carval-García; Daniela Sabalza-Pérez; Jean Caratt-Ortiz; Nelly De Armas-Calderón; Andrés Rodríguez-Toscano; Howen Anguiano-González (Center of Biomass & Renewable Energy (CBIORE), 2026)
Absorption refrigeration systems are increasingly recognized as sustainable alternatives for cooling applications, particularly when integrated with renewable energy sources such as solar thermal systems. Among the available working pairs, the NH₃–NaSCN solution offers favorable thermodynamic properties and low environmental impact; however, its performance under tropical climatic conditions with solar integration remains insufficiently explored. This study evaluates the thermodynamic and exergetic performance of a single-effect NH₃–NaSCN absorption refrigeration cycle integrated with a flat-plate solar collector, considering the climatic conditions of five cities of the Colombian Caribbean Region. A validated thermodynamic model was applied to assess the influence of generator, condenser, absorber, and evaporator temperatures on the coefficient of performance (COP) and exergetic efficiency. Results show that increasing generator temperature from 75 °C to 120 °C enhances COP by up to 46.15 %, while raising the evaporator temperature from –8 °C to 4 °C improves COP by 16 %. Conversely, increasing condenser and absorber temperatures reduce COP by 20.54 % and 16 %, respectively. Exergy destruction analysis indicates that the generator and absorber account for 55 % and 34 % of total irreversibilities, highlighting them as priority targets for optimization. Analysis of variance identified generator temperature as the most influential parameter on COP (39.37 %), followed by condenser (31.22 %) and evaporator temperatures (15.18 %). Solar integration enabled stable operation with an average COP decrease of only 3 % across the five cities; however, the use of water in the solar collector restricted operation below the optimal efficiency range (95–120 °C). The combined performance index integrating COP and exergetic efficiency showed that the operating range characterized by elevated generator temperature and reduced condenser temperature delivers the best energy–exergy trade-off, providing design guidelines for high-irradiance regions and supporting the adoption of NH₃–NaSCN as a cost-effective, renewable refrigeration solution.